An application of satellite tracking technologies to conserve wildlife : a case study approach : a dissertation presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Natural Resource Management at Massey University, Palmerston North, New Zealand - Thomas, Bindi; Thomas, Bindi (Massey University, 2010)
Wildlife management is an important area of conservation and has become a priority for many countries and organisations around the world. One of the fundamental components of a sound wildlife management plan is a good understanding of a species’ behaviour and habitat. For animals within inaccessible environments, satellite tracking provides a powerful tool for revealing information on animal movements and their habitat requirements. In this dissertation, the conservation benefits and technical effectiveness of satellite tracking are examined through four case studies representing a diverse range of threatened species studied for periods between six months and five years. The studies revealed important ecological insights on the in situ movement and behaviour of the African elephant (Loxodonta africana), Kruger National Park, South Africa; the New Zealand bush falcon (Falco novaeseelandiae), Central North Island, New Zealand; the estuarine crocodile (Crocodylus porosus), Darwin, Australia; and the northern royal albatross (Diomedea sanfordi), Taiaroa Head, New Zealand and Chile. For each of these studies, satellite telemetry provided location data enabling analyses of the animals’ movements and home ranges, and these analyses inform specific management recommendations. For example, the long time series study on African elephants highlighted the importance of developing reciprocal animal management policies where cross-boundary movements of animals occurred between adjacent parks. The strengths and weaknesses of different satellite tracking systems are compared and guidelines developed to assist wildlife managers in selecting the best technology to suit their research needs. An assessment of the trade-offs between the technical features built into transmitters and the associated cost is also presented. The study shows how the use of satellite tracking systems provides conservation agencies with a better understanding of wildlife behaviour and strengthens their ability to improve wildlife management planning.
Keywords: Wildlife conservation; African elephants; New Zealand falcon; Northern royal albatross; Crocodile; Home range; Migration; Animal behaviour; Global Positioning System; Animal tracking